First Exhaustive Catalog of Spiders of Algeria (Arachnida: Araneae) - Beladjal, Lynda; Bouseksou, Samira; Kherbouche-Abrous, Ourida; Alioua, Youcef; Bosmans, Robert (Zootaxa, 2025)
The authors present a catalog of spider species in Algeria, documenting 893 species belonging to 315 genera in 52 families. For each species, a detailed list of all localities cited in the literature is provided, along with full references. All data are examined and critically analysed using the most recent available information. Of the 893 species, 245 (27.44%) are known only from Algeria and are considered endemic. According to the World Spider Catalog (2024) and the present work, 12 species are nomina dubia, 114 species are not included and 8 have to be omitted from the Algerian list. Although this number of species is large, knowledge of the Araneofauna in Algeria is still progressing. Several new records and new species are in the process of being described, and many more will certainly be described shortly. This confirms that Algeria is very rich in terms of spider species.